In Vivo Thermographic Analysis of the Corneal Surface in Keratoconic Patients Undergoing Riboflavin–UV-A Accelerated Cross-Linking. Issue 3 (March 2015) - Mencucci, Rita; Mazzotta, Cosimo; Corvi, Andrea; Terracciano, Luca; Rechichi, Miguel; Matteoli, Sara
Abstract : Purpose: To assess corneal thermal profile during combined riboflavin and accelerated UV corneal collagen cross-linking (A-CXL) using in vivo surface thermographic analysis. Methods: In this open-label, nonrandomized, prospective pilot study, 28 eyes of 28 patients were included. The study was conduced at the Department of Surgery and Translational Medicine, University of Florence, Italy, in collaboration with the Ophthalmic Operative Unit of Siena University, Italy. All patients underwent high-fluence A-CXL in pulsed light and continuous light UV-A exposure at 30 and 18 mW/cm 2 . Patients were divided into 4 groups: 7 for continuous light A-CXL, 7 for pulsed light A-CXL at 30 mW/cm 2 with 7.2 J energy, 7 for continuous light A-CXL, and 7 for pulsed light A-CXL at 18 mW/cm 2 with 5.4 J energy. Corneal surface temperature measurements were recorded using an infrared FLIR thermocamera (FLIR 320A; FLIR Systems). Corneal temperature values were detected in the surface area exposed to UV-A light irradiation, selecting it in the acquired thermographic image. The maximum temperature value detected in the area studied was recorded and considered for comparative analysis. Results: Infrared thermocamera measurements of the corneal surface during A-CXL treatments showed an average temperature of 31.5°C during the entire procedure in all groups and UV-A powers (30 mW/cm 2 at 7.2 J/cm 2 and 18 mW/cm 2 at 5.4 J/cm 2 ) and light exposure modality remained under the threshold of collagen thermal injury. Conclusions: Accelerated corneal collagen cross-linking did not cause thermal rise over the threshold of thermal injury to the corneal surface, demonstrating a safe thermal profile both at 30 mW/cm 2 with 7.2 J and 18 mW/cm 2 with 5.4 J energy dose.